Understanding the Performance of Multilane Expressway Exit Design and a Traffic Organization Strategy Based on VISSIM Micro-Simulation and a Comprehensive Evaluation Method - Qiaoliang Chen; Binghong Pan; Yutong Liu (Applied Sciences, 2023)
Frequent consecutive lane changes and the barrier effect produced by trucks can always contribute to rapid access to the capacity bottleneck at expressway exits, thereby reducing operational performance. This paper proposes to retrofit the conventional interchange design to reduce lane changes and compares them with conventional design and passenger vehicle and truck separation (PVTS) design from multiple fields via VISSIM numerical simulation, which is developed and calibrated with traffic data collected on the eight-lane expressway in China at four levels of service (LOS). Comprehensive evaluation (CE) results reveal that the PVTS strategy improves operational performance by 10–20% at multilane expressway exits, while lane separation around interchanges also yields a similar gain. However, ramps on both the left and right sides show less effective improvement and are even negative at LOS-A and LOS-B. All PVTS and improved designs produce a better comprehensive improvement ratio with a LOS decrease, and improved designs achieve optimal performance below LOS-B with construction cost taken into consideration.